مؤشرات التفكير النقدي في علم الرجال من بداية القرن الأول حتى منتصف القرن الثاني عند الإمامية - عبدالغرابي، عبدالله محسن; أصل، علي أسدي; رئيسيان، غلام رضا (الجامعة الإسلامية, 2024)
إن علم الرجال قد مر في بلورته وتطوره وتدوينه بمراحل عديدة، بدايتها مرحلة النشأة والتدوين حتى منتصف القرن الثاني، ولم يسلط الضوء عليها بشكل مجز وكاف، كما سلط الضوء على ما وصل إلينا من أصول رجالية بدعوى عدم الحاجة لذلك، لأن ما بأيدينا مغن عنها، ولا توجد ضرورة لبحثها. والواقع أن هذا فتح الباب أمام الكثير من الشبهات والإشكالات، التي وجهت للتراث الروائي تارة، وإلى مدرك حجية قول الرجالي تارة أخرى. وهذا يستدعي غلق الباب أمام هذه التساؤلات والإشكالات والشبهات، وإزاحة الغبار عن هذه الفترة الرمادية في تاريخ علم الرجال، وذلك بإثبات وجود أصول وجذور ومؤشرات هذا العلم في مدرستنا من زمن النص القرآني وعصر النبي صلى الله عليه وسلم والأئمة عليهم السلام، وتعاقب أصحابهم (رضوان الله عليهم) عليه، كابر عن كابر، من خلال النقد للناقلين، وتتبع أحوالهم، وتحديد صفاتهم، وما يتعلق بجرحهم أو تعديلهم، بشكل مباشر، من خلال استقراء وتحليل الشواهد والأدلة التي تؤكد وجود جذور رجالية موازية لعصر النص المبارك، والنبي الأعظم والأئمة عليهم السلام. The science of men has passed through its crystal, its development and its codification in many stages, the beginning of the stage of origin and blogging until the middle of the second century, and it was not highlighted in a way that is rewarded and sufficient. There is no need to research it. Indeed, this opened the door to many suspicions and problems, which were directed to the narrative heritage sometimes, and to the perception of the Hajj of the men of the men at other times. This requires closing the door to these questions, problems and suspicions, and removing dust from this gray period in the history of men's science, by proving the existence of origins, roots and indicators of this science in our school, from the time of the Qur’anic text and the era of the Prophet (may God bless him and his family and peace) and the imams (peace be upon them) And their companions (may God be pleased with them) punish him, Kabir from Kaber, through criticism of the carriers, follow their conditions, and determine their attributes, and what relates to their wound or amendment, directly, through extrapolation and analysis of evidence and evidence that confirms the existence of men parallel to the era of the blessed text, And the greatest Prophet and the imams, peace be upon him.
Keywords: الشريعة الإسلامية -- الأحاديث النبوية -- المذاهب الفقهية -- التفكير النفدي